Penguatan Literasi, Kreativitas, dan Solidaritas Siswa melalui PjBL di SDN Wonosuko 4, Bondowoso - Aldya Zahra Nur Naqiyah; Aurelia Cintania Amir; Adelia Sakita; Daliah Humam Bafadal; Nailah Faiqoh Al Adibah; Variel Adi Kusuma Putra; Zakiyatus Sholiha; Dyta Agnes Layung Sari; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The literacy, creativity, and solidarity enhancement program took place at SD Negeri Wonosuko 4 over a three-week period, involving 42 students from grades III to V in activities that included shared reading sessions, simple creative-product tasks, and collaborative educational games. Assessment instruments comprised literacy observation sheets, product-quality rubrics, and attitude scales measuring cooperation, with key success indicators encompassing independent reading frequency, visual product quality, and teamwork scores during group activities. Pre-test and post-test results revealed a 2% increase in literacy skills, a 3% rise in creative participation, and a 2% improvement in cooperation indicators, while qualitative findings—such as heightened reading enthusiasm, enhanced confidence in expressing ideas, and strengthened group communication—reinforce the conclusion that practice-based learning effectively promotes both academic and social development. The program demonstrates that interactive and contextual approaches can strengthen foundational literacy while cultivating collaborative character among primary school students.